Efforts to Provide National Hybrid Corn Seed for Farmers in Gold Mining Area. Issue 1 (1st January 2023) - Bahtiar,; Azrai, M; Salman, D; Arsyad, M
Abstract: Facing public objections to the existence of the PT Gold Mine Company. Meares Soputan Mining/Tambang Tondano Nusajaya (MSM/TTN), then in 2019 the manager of the Corporate Social Responsibility (CSR) fund collaborated with the Indonesian Cereal Research Institute (ICERI) to foster farmers to produce hybrid corn seeds in order to meet the needs of farmers around the company. The two activities carried out are: the practice of making hybrid corn seeds and demonstration plots farming of the seed yield. The practice of making seeds is carried out in PT.MSM/TNT's 1.0 ha. Implementers are trained in Standard Operational Procedure (SOP) for corn seed production hybrid and accompanied in the field during activities: planting, selection (Roguing), removal of male flowers (Detasseling) and at harvest. The seeds produced were the Nakula Sadewa (Nasa-29) variety with consideration of the suitability of location characteristics with varietal potential. The yield is 1.0 ton with very good seed quality (99% germination). The 250 kg of seeds were used for demonstration plots farming area of 10 ha in the following planting season, involving 110 farmers spread over 8 villages around the mining area of PT. MSM/TNT. Farm demonstration plot results showed that, the Nasa-29 variety gave good growth with productivity levels achieved between 6.73 t/ha to 7.52 t/ha. This level of production is relatively high compared to the level of production local seed, only ranging from 4.25 t/ha to 5.65 t/ha. The response of farmers to the appearance of the Nasa-29 variety was positive so that the CSR manager of PT.MSM/TNT increased the area of seed production to 5.0 ha in 2020.